Approaches to Online Evaluation in Higher Education in the Emergency Shift of COVID – 19: An Empirical Study of West Bengal - Chattopadhyay, Reshmi; Sen, Pronay; Gurung, Pratistha; Maity, Bireswar; Bhowmik, Sunandita (International Journal of Social Sciences and Management, 2023)
This paper tried to assess the approaches adopted in online evaluation system during COVID 19 pandemic in higher education. Day to day teaching learning as well as the evaluation system have been significantly affected during the emergency shift of COVID 19. The main objectives of this paper were to study the different practices of evaluation system; its, validity and effectiveness; and institutional preparedness to conduct the whole process of online evaluation. The paper also highlighted the issues and challenges faced by the students during formative and summative evaluation. Self-made online questionnaire was distributed to the college and university students and teachers of West Bengal. Descriptive survey method was used to collect data and simple percentage analysis was used for data analysis. It is found that the system was not ready for the rapid change. Sudden changes made the evaluation system a mess. The summative evaluation followed the same pattern of question papers. Only the pattern of formative evaluation was different. Online media and devices were used rigorously. This emergent shift in evaluation in turn has encouraged students to copy from internet. Unethical issues were present due to the absence of the teachers. That leads to several misconducts and cheating. Higher education institutions followed their own customized system for evaluation. Students’ satisfaction and institutional preparedness were also not up to the mark. It was failed to differentiate between the high and low achievers.